ABM Proceedings 2017
DOI: 10.5151/1982-9345-30380
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Titanium Nitrides Formed During Steel Solidification

Abstract: For certain applications, coarse titanium nitride (TiN) precipitates can be deleterious for the final properties of the material. Hence, in order to better understand the mechanisms involved in the generation of these precipitates, a thorough characterization of the particles observed in steels with different titanium and nitrogen content was carried out. Samples from liquid steel (tundish), continuous casting billets and final product were evaluated using an Automatic Particle Analyzer (APA) coupled to a Scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Existence of the gases in molten steel can cause major problems for steelmakers and engineers such as reducing the plasticity, strength, and resistance against the erosion of the steel. In this regard, applying a vacuum in order to draw and remove the gases from the melt can prevent the mentioned problems whose process is called the vacuum degassing (VD) process [2][3][4]. The VD process requires a deep vacuum up to 0.5 Torr (0.67 mbar) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Existence of the gases in molten steel can cause major problems for steelmakers and engineers such as reducing the plasticity, strength, and resistance against the erosion of the steel. In this regard, applying a vacuum in order to draw and remove the gases from the melt can prevent the mentioned problems whose process is called the vacuum degassing (VD) process [2][3][4]. The VD process requires a deep vacuum up to 0.5 Torr (0.67 mbar) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…This reduced the depth of impingement of the molten steel jet and accelerated inclusion flotation processes. In another study, Capurro et al 6 investigated the effect of a new SEN with six lateral ports on the distribution of inclusions in finished cast products. They reported that lower density of inclusions was found in products cast with the newly designed SEN in comparison with a straight, singleport nozzle.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that lower density of inclusions was found in products cast with the newly designed SEN in comparison with a straight, singleport nozzle. In recent years, Morales et al [6][7][8][9] developed a fluid flow model to study the effect of new SEN designs on mold powder entrainment (MPE) for both round and square billet casting processes. Based on their numerical and physical modeling results, their proposed curved ported SEN could reduce the risk of MPE, due to swirling flows created in the mold cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Y en la medida en que la posición se acerca al nodo O el cociente se incrementa ligeramente hasta alcanzar un máximo valor. Capurro y col. [110] para un lingote circular de acero con alto contenido de de diámetro 150 mm y altura 550 mm, realizan un estudio experimental de la evolución de , y . Asimismo, Karlinski y col. [21] en una palanquilla de sección cuadrada de 150x150 , desde la superficie de la palanquilla hasta el nodo origen realizan un ajuste lineal del cociente .…”
Section: 372-simulación Numérica De Los Espaciados Dendríticos Aplica...unclassified
“…En la Fig. 3.33 , se observa que en la medida en que aumenta la velocidad de enfriamiento , el cociente disminuye, la misma tendencia ha sido observada por Capurro y col. [110] y Karlinski de Barcellos [21] , sin embargo, ésta difiere con la publicada por Wolf [108] y Guo y Zhu [104] .…”
Section: 373-distribución Del Cociente Entre El Espaciado Dendrítico ...unclassified